The Role of the Deposit Insurance Corporation in Driving Indonesian Banking toward TNFD Disclosure: Strategies and Policy Implications - Utami, Pertiwi; Purnamasari, Sinta Ayu; Ramatullah, Risen anugrah; Zais, Ferliansyah (LP2M IBK Nitro, 2025)
This study aims to analyze the strategic role of the Deposit Insurance Corporation (LPS) in encouraging the adoption of the Taskforce on Nature-related Financial Disclosure (TNFD) framework by the Indonesian banking sector. Although TNFD has become the global standard for reporting nature risks, to date no national bank has officially joined this initiative. The study employed a systematic literature review approach, supported by bibliometric analysis using VOSviewer software, to identify trends, research gaps, and thematic linkages within global TNFD studies. The findings indicate that the main challenges to TNFD adoption in Indonesia include an unclear regulatory framework, limited environmental data infrastructure, low awareness and capacity of banking human resources, and a lack of institutional incentives. This study proposes five collaborative strategies that LPS can implement: the establishment of a national TNFD forum, a sustainability-based premium incentive scheme, data and technology collaboration, mentoring and certification programs, and innovation in nature-based risk assurance. This study contributes to academic discourse and public policy by introducing a new role model for LPS as a catalyst for sustainable finance transitions in developing countries.